PENDAMPINGAN PENGOLAHAN LIMBAH CAIR ZAT WARNA ALAMI BATIK PADA CV ULUR WIJI MUDA BERDAYA KABUPATEN MOJOKERTO - Susanto Susanto; Haris Puspito Buwono; Luchis Rubianto; Windi Zamrudy; Dwina Moentamaria; Mutia Devi Hidayati; Agus Jalaluddin (P3M Politeknik Negeri Malang, 2025)
In Kemlagi District, Mojokerto Regency, a small and medium-sized batik enterprise, CV Ulur Wiji Muda Berdaya, has gained popularity among millennials due to its use of natural dyes that are environmentally friendly. The products have not only attracted domestic consumers but have also reached international markets. Despite this achievement, the enterprise continues to face a major challenge in managing batik dye wastewater, which has not received optimal treatment. To solve this issue, a community service program was implemented to provide technical assistance in wastewater treatment through training on filtration adsorption methods for the employees of CV Ulur Wiji. The filtration unit employed adsorption media consisting of foam filters, zeolite, activated carbon, coral stone, and Malang sand. The questionnaire results confirm that the partner has improved the application of wastewater treatment technology as a result of the program. The results of batik waste processing indicated an improvement in the waste quality, changing from a turbid color to a clearer appearance, with an initial pH of 6.3; after undergoing filtration-adsorption, the pH shifted to near neutral at 6.9. Furthermore, an additional outcome of this program is the successful development of an appropriate technology system for treating wastewater from batik dye using filtration–adsorption techniques.